Studying Tag Vocabulary Behaviour of Social Tagging Systems in Learing Object Repositories - Zervas, P.; Sampson, Demetrios; Pelliccione, Lina (2016)
In the field of Technology-enhanced Learning (TeL), social tagging has been applied to Learning Object Repositories (LORs) mainly as a means:(a) to offer an alternative way of classifying the Learning Objects (LOs) based on the tag vocabulary created by the end-users of the LOs, and (b) to facilitate the enhancement of LOs’ descriptions via collaborative tagging. However, in order to be able to understand how a social tagging system performs and whether it can deliver the aforementioned goals, it is important to be able to investigate the evolution of the tag vocabulary, which constitutes the core component of a social tagging system. Within this context, research has focused on different facets of social tagging systems such as the growth of the tag vocabulary, the frequency and reuse of tags, as well as the stability of the tag vocabulary but there are only sporadic studies for investigating these issues in the field of LORs. This paper aims to contribute in studying how social tagging systems perform in the context of LORs by investigating the evolution of the tag vocabulary in OpenScienceResources Repository, a science education domain specific repository with a rich dataset operating in Europe for 5 years.